(3dhGeY GdHjfGJ aj TQM GdCSeGA hGdUaGJs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi UGQJ GdCacGQ ai eHGOF CfhGQ cHQjGFg CeG HYO aEf Gddg JYGdi deG CeQfi HGdGJUGd HMVQI GdSdWGf s
(3BNQgG (B:s
(3GdKGdK GdYRe hgh JhWjf GdfaS HYO GdJQOO GdPi efTCg GdLgd JeJ GdcJGH s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1569s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds